ANALISIS FAKTOR PRIORITAS DALAM PEMILIHAN PERUMAHAN KPR MENGGUNAKAN METODE AHP - Zulfi Azhar; Masitah Handayani (Jurnal Manajemen Informatika dan Sistem Informasi, 2018)
The high public interest in the ownership of decent and cheap housing, so fertile the business of Kredit Perumahan Rakyat (KPR). The rapid growth of housing-based mortgages due to the subsidy from the government so that people have the ease of a minimum of the price. Even sometimes found housing developers who offer low-cost advance materials until no down payment. As a result, the quality of buildings, facilities, and legality rumahpun sidelined. This will obviously harm society in the future. Therefore, the community must have the ability in determining the KPR which with various criteria that will be able to prevent society from loss. This study aims to analyze the factors of priority in the selection of housing KPR. This method is done through the application of Analytical Hierarchy Process (AHP) method. Based on the results of the calculation analysis that has been done, then sequentially the criteria that the highest priority is the criteria of Building Quality, House Price, Advances, Location, Licensing, and Facilities.